A small-sized benzothiazole–indolium fluorescent probe: the study of interaction specificity targeting c-MYC promoter G-quadruplex structures and live cell imaging. Issue 95 (13th November 2020) - Zheng, Bo-Xin; She, Meng-Ting; Long, Wei; Xu, Yong-Yu; Zhang, Yi-Han; Huang, Xuan-He; Liu, Wenjie; Hou, Jin-Qiang; Wong, Wing-Leung; Lu, Yu-Jing
Abstract : A small-sized and target-specific fluorescent probe reveals the presence of c-MYC DNA G4-structures in cells and shows anticancer activity. Abstract : A small-sized c-MYC promoter G-quadruplex selective fluorescent BZT-Indolium binding ligand was demonstrated for the first time as a highly target-specific and photostable probe for in vitro staining and live cell imaging and it was found to be able to inhibit the amplification of the c-MYC G-rich sequence (G-quadruplex) and down-regulate oncogene c-MYC expression in human cancer cells (HeLa).